THE INFLUENCE OF THE HEDONISTIC LIFESTYLE ON DECISIONS PURCHASES ON COMPASS SHOE PRODUCTS ON SHOPEE E-COMMERCE - Rajasa, Ilham Surya; Hermawan, Haris; Sari, Maheni Ika (Dynamic Management Journal, 2024)
This research aims to determine and analyze the influence of hedonic lifestyle dimensions (activities, interests and opinions) on purchasing decisions for Compas shoe products via E-commerce. The sample used in this research was Compass shoe customers. This type of research uses quantitative methods with a sample size of 95 respondents and uses non-probability purposive sampling techniques using data collection techniques in the form of questionnaires to respondents. The data analysis technique for this research uses instrument testing, classical assumptions and multiple linear regression. The analysis results obtained show that activities, interests and opinions have a positive and significant influence both partially and simultaneously on the decision to purchase Compass shoes, with a contribution level of influence of 0.729 or 79%.